2010
DOI: 10.1007/s12094-010-0553-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal toxicity associated to radiation therapy

Abstract: Radiation therapy in combination with other treatments, such as surgery and chemotherapy, increases locoregional control and survival in patients with thoracic, abdominal and pelvic malignancies. Nevertheless, significant clinical toxicity with combined treatments may be seen in these patients. With the advent of tridimensional conformal radiotherapy (3D-CRT), dose-volume histograms (DVH) can be generated to assess the dose received by the organs at risk. The possible relationship between these parameters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 104 publications
(54 reference statements)
0
12
0
1
Order By: Relevance
“…70 Radiation dose ≥30 Gy (inclusive of any TBI) is a risk factor for stricture formation. 70;71 Additional risk factors for esophageal stricture specifically include chronic GVHD, prior candida esophagitis, and gastroesophageal reflux. 70;72 Late bowel obstruction can be seen many years after abdominal surgery.…”
Section: Gastrointestinalmentioning
confidence: 99%
“…70 Radiation dose ≥30 Gy (inclusive of any TBI) is a risk factor for stricture formation. 70;71 Additional risk factors for esophageal stricture specifically include chronic GVHD, prior candida esophagitis, and gastroesophageal reflux. 70;72 Late bowel obstruction can be seen many years after abdominal surgery.…”
Section: Gastrointestinalmentioning
confidence: 99%
“…Importantly, radiation therapy remains a mainstay in the management of cancer, a leading cause of death worldwide. Radiation therapy destroys rapidly proliferating cancer cells and, inevitably, normal tissues characterized by continuous regeneration programs, including hair follicles, bone marrow, the GI tract as well as other glandular epithelia (5). In that context, dose-limiting toxicities of radiation discourage patients from completing therapy; restrict maximum doses of radiation which limits the efficacy of treatment; and can lead to chronic morbidity and mortality (5).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The mechanism is believed to be primarily an increased delivery of O 2 up to the injured intestinal tissue to promote faster healing, enhance immunity, and prevent colonization of harmful bacteria. 13 Albenberg et al demonstrated convincingly that hyperbaric O 2 therapy also alters the host mucosal bacterial communities and may provide further protection against pathogenesis by potential pathobionts in the gut. More research is needed to assess the functional role of hyperbaric O 2 -induced microbiota and whether this therapy may be beneficial in the co-management of patients with chronic intestinal inflammation or injury.…”
mentioning
confidence: 99%